Asset management excellence : optimizing equipment life-cycle decisions - Campbell, John D.; Jardine, Andrew K. S.; McGlynn, Joel (Boca Raton : CRC Press, 2011)
Globalization, consolidation, and changes in technology challenge asset management and maintenance professionals to be more efficient. This book provides coverage of leadership issues, the implementation of new processes, and change management
1. Maintenance management fundamentals -- 2. Managing equipment reliability -- 3. Optimizing maintenance decisions -- 4. Achieving maintenance excellence
Previous ed. published under title: Maintenance excellence, 2001
Includes bibliographical references and index
Keywords: Product life cycle; Production engineering; Production management